140k views
5 votes
Do I use pemdas for this problem, if I do, how would I solve it with it?

Do I use pemdas for this problem, if I do, how would I solve it with it?-example-1

1 Answer

6 votes

Answer:

PEMDAS does apply but not with the parentheses

The answer is −3g−4 btw

Step-by-step explanation:

Let's simplify step-by-step.

−2g+7−(g+11)

Distribute the Negative Sign:

=−2g+7+−1(g+11)

=−2g+7+−1g+(−1)(11)

=−2g+7+−g+−11

Combine Like Terms:

=−2g+7+−g+−11

=(−2g+−g)+(7+−11)

=−3g+−4

User Djuarezg
by
6.1k points